Factors Responsible for Depression in Patients with Chronic Obstructive Pulmonary Disease - Yasir Ahmed, Saadia Ashraf, Taimur Zeb, Waqas Ahmad, Shahid Zia, Muhammad Fayaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a neglected but important health problem, accounts for significant morbidities and mortalities worldwide. By year 2030, it is expected to be the third leading causing of mortality. COPD patients with associated depression can affect disease progression, high healthcare resource utilization, more frequent exacerbations and increased mortality. Objectives: To determine the frequency of factors leading to depression in patients with COPD presenting to tertiary care hospital at Peshawar. Material & Methods: It was descriptive Cross-Sectional Study conducted at Pulmonology unit,Khyber teaching hospital Peshawar from 12th November 2019 to 12th May 2020.Patients with COPD fulfilling the inclusion criteria were assessed for depression. A total of 43 patients were selected according to Hamilton Depression Rating Scale (HDRS 21) for Depression. Factors leading to depression like Gold stage of COPD, smoking, socio economic status, mMRC grades of dyspnea and C reactive proteins level were assessed. Frequency was calculated for each of these factors causing depression. These factors were further stratified on basis of age, gender, duration of COPD and no of hospitalization. SPSS version 22 was used for analyzing of the collected data. P value less than 0.05 was marked as statistically significant. Results: Among these 43 COPD patients with depression, 19 (44.2%) were males and 24 (55.8%) were females. Mean age was 61.93 years (45-80) ± 10.30 SD. Frequency of Gold stage of COPD was stage II (16.3%), stage III (58.1%) and stage IV (25.6%). Frequency of smoking was 37.2%. CRP level was raised in 58% of patients. mMRC grades of dyspnea were grade II (18.6%), grade III (44.2%) and grade IV (37.2%) and 67.4% of the patients were poor. On post stratification of smoking on the basis of gender, and Gold stages of COPD on the basis of number of hospitalization, p value was 0.02 and 0.01 which was significant statistically. Conclusion: It concludes that GOLD stage of COPD, smoking, increased CRP level, increased Dyspnea (MMRC scale) and poverty are the factors leading to depression in patients with COPD, affecting quality of life and progresion of COPD. Keywords: Chronic obstructive pulmonary disease, depression, GOLD.